Life after trauma in aceh: consequences and therapies - Yulia Direzkia (Procedia : Studi Kasus dan Intervensi Psikologi, 2015)
Longstanding war conflict in Aceh as well as the earthquake and tsunami in 2004 not only resulted in many deaths and destruction in many other aspects of life. In 2012-2013 this study was conducted to determine the events related to the trauma experienced by children in Aceh, consequencesand effectiveness of a psychotherapy. Intervention was given using the Eye Movement Desensitization and Reprocessing (EMDR). A total of 56 children from Banda Aceh and Aceh Besar were taken as samples of this study, with an age range of 5 to 17 years. To measure the effectiveness of the therapy treatment used the Children Behavior Checklist (CBCL) with 112 items for older children from 11 years on and the standard CBCL for smaller kids. The CBCL versions used the Indonesian language that has been validated. In other hand, the traumatic stressors was obtained from a list of Traumatic Events. The result shows that based on the large number of events, then the order of the highest number of cases was traumatized by the earthquake and tsunami (20%), domestic violence (15%), war conflict (13%), bullying (13%), accident (8%) , lost (4%) and trafficking (2%). Almost 75% of all children have improved in their condition and become more adaptive or in other word belong now in the “normal” category. The improvement is there can then be attributed to the therapy. About 25% remains in a clinical or borderline condition.Keywords: trauma, Eye Movement Desensitization and Reprocessing therapy, effectiveness